1997
DOI: 10.1111/j.1432-1033.1997.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Oxidation Provoked by Endotoxins Treatment is Suppressed by Feeding Ascorbic Acid in a Rat Mutant Unable to Synthesize Ascorbic Acid

Abstract: We examined the possibility that bilirubin oxidation is provoked in vivo by using scurvy-prone ODSodlod rats treated with endotoxin (lipopolysaccharide). Recently, bilirubin oxidative metabolites were isolated from human urine and named biotripyrrin-a and biotripyrrin-b. In ODs-odlod rats fed an ascorbicacid-free diet, the concentration of bilirubin metabolites in urine was increased 7.0-fold at 3 h after injection of lipopolysaccharide and 4.4-fold at 10 h compared to the control rats injected with saline. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 37 publications
4
32
0
1
Order By: Relevance
“…It is known that reactive oxygen intermediates are second messengers in the activation of NF-B ( 21 ) and included in the stimulation of inflammatory cytokine gene expressions. Ascorbic acid has a capacity to scavenge reactive oxygen intermediates, and is a physiological compound exhibiting this capacity ( 22 ). In the liver of ascorbic acid-deficient ODS rats, it is speculated that the increase in the amount of reactive oxygen intermediates might cause the activation of NF-B, leading to the stimulation of CINC-1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that reactive oxygen intermediates are second messengers in the activation of NF-B ( 21 ) and included in the stimulation of inflammatory cytokine gene expressions. Ascorbic acid has a capacity to scavenge reactive oxygen intermediates, and is a physiological compound exhibiting this capacity ( 22 ). In the liver of ascorbic acid-deficient ODS rats, it is speculated that the increase in the amount of reactive oxygen intermediates might cause the activation of NF-B, leading to the stimulation of CINC-1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Conceivable explanations for the early elevation of urinary biopyrrin level could be serum bilirubin oxidation or increased hemolysis during the inflammatory process after MIR. Yamaguchi et al found that increased bilirubin oxidation precedes HO-1 upregulation in a lipopolysaccharide-treated rat model 36 and Morita et al discovered that serum bilirubin levels significantly decrease after the spasm provocation test in patients with ischemic heart disease. 33 Those reports support the notion that biopyrrins are synthesized as a result of serum bilirubin oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Biopyrrins are immediately excreted in urine because of their hydrophilic properties and thus can reflect the severity of oxidative stress. 25,[32][33][34][35][36][37][38] Biopyrrin synthesis reflects NO radicals, 25 so urinary biopyrrin levels can indicate ongoing changes in oxidative stress in vivo and thus function as a marker of oxidative stress.The time course of urinary and tissue biopyrrin levels in rat models of cardiac transplantation and hepatic ischemia reperfusion has been investigated. 25,32 A cardiac transplantation study showed that levels of urinary biopyrrins become more rapidly and sensitively elevated than either urinary 8-hydroxy-2'-deoxyguanosine or serum troponin-T during …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, bilirubin has anti-oxidative effects. 12,13) The increasing levels of fecal pigment seen after Ge-132 ingestion suggest the enhancement of bilirubin excretion in the intestine. In this study, we first compared the color of the cecal pigment of rats.…”
Section: Introductionmentioning
confidence: 99%